2005
DOI: 10.1021/jp052284l
|View full text |Cite
|
Sign up to set email alerts
|

Selective Growth of Ag Nanowires on Si(111) Surfaces by Electroless Deposition

Abstract: Electroless deposition of Ag on atomically flat H-terminated Si(111) surfaces in aqueous alkaline solutions containing Ag ions produced two different sizes of Ag nanowires along atomic step edges: (1) a narrow nanowire of 10 nm in width and 0.5 nm in height and (2) a wide nanowire of 35 nm in width and 11 nm in height. The narrow and wide nanowires were formed by immersion in the solutions containing less than 1 ppb and 8 ppm dissolved-oxygen concentrations, respectively. This result indicates that the dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…4,5 Liquid−liquid phase separation of organic salts (ionic liquids) mixing with small organic molecules is also of great importance, especially in catalysis 6,7 and separation. 8,9 For instance, the biocatalytic synthesis of 16 flavor esters 10 or monoacylglycerides 11 can be carried out in specific ionic liquids and separated through liquid−liquid phase separation. Similar procedures were also found when mixing ionic liquids with other small organic molecules such as neryl acetate 12 and immobilized lipase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Liquid−liquid phase separation of organic salts (ionic liquids) mixing with small organic molecules is also of great importance, especially in catalysis 6,7 and separation. 8,9 For instance, the biocatalytic synthesis of 16 flavor esters 10 or monoacylglycerides 11 can be carried out in specific ionic liquids and separated through liquid−liquid phase separation. Similar procedures were also found when mixing ionic liquids with other small organic molecules such as neryl acetate 12 and immobilized lipase.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid–liquid phase separation is of great importance in many fields of chemistry, chemical engineering, biology, physics, and materials science. For instance, liquid–liquid phase separation can be used for membrane preparation, , liquid catalysis, and providing separated environment for complex bio–chemical interactions in cell. , Liquid–liquid phase separation of organic salts (ionic liquids) mixing with small organic molecules is also of great importance, especially in catalysis , and separation. , For instance, the biocatalytic synthesis of 16 flavor esters or monoacylglycerides can be carried out in specific ionic liquids and separated through liquid–liquid phase separation. Similar procedures were also found when mixing ionic liquids with other small organic molecules such as neryl acetate and immobilized lipase .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] We have reported that atomic metal wires could be fabricated along step edges by the wet process. [5][6][7] To obtain well-controlled nanostructures, however, some advanced methods of template preparation with a given step structure are required. It is thus necessary to understand wet etching kinetics during step-terrace preparation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a promising approach to exploiting the SERS effect of the 2D Au nanoplates involves integrating them with a solid substrate. As a result of this need, extensive exploration has been undertaken in recent years; however, most of the employed methods are restricted by a two‐step route (synthesizing Au nanoplates first and then casting them on the surface of a solid substrate). Alternatively, simultaneous synthesis and immobilization of Au nanoplates on the selected matrix has been attractive because of great convenience and efficiency.…”
Section: Introductionmentioning
confidence: 99%